Recombinant FSH glycoforms are bioactive in mouse preantral ovarian follicles. Issue 6 (December 2019) - Simon, Leah E; Liu, Zhenghui; Bousfield, George R; Kumar, T Rajendra; Duncan, Francesca E
Abstract : Female reproductive aging is characterized by a rise in follicle-stimulating hormone (FSH) levels during peri-menopause. N-linked glycans are co-translationally attached to the Asn 7 and Asn 24 residues on the FSHβ subunit. Differences in the number of N-glycans on the FSHβ subunit result in distinct glycoforms: hypo-glycosylated (FSH 21/18, glycans absent on either Asn 24 or Asn 7, respectively) or fully-glycosylated (FSH 24, glycans present on both Asn 7 and Asn 24 ). The relative abundance of FSH glycoforms changes with advanced reproductive age, shifting from predominantly FSH 21/18 in younger women to FSH 24 in older women. Previous in vitro studies in granulosa cell lines and in vivo studies using Fshb -null mice showed these glycoforms elicit differential bioactivities. However, the direct effects of FSH glycoforms on the mouse ovarian follicle have not yet been determined. In this study, we isolated secondary follicles from pre-pubertal mice and treated them with 20- or 100 ng/mL purified recombinant FSH glycoforms for 1 h or 18–20 h. Analysis of phosphorylated PKA substrates showed that glycoforms were bioactive in follicles following 1-h treatment, although differential bioactivity was only observed with the 100 ng/mL dose. Treatment of follicles with 100 ng/mL of each glycoform also induced distinct expression patterns of FSH-responsive genes as assessed by qPCR, consistent with differential function. Our results, therefore, indicate that FSH glycoforms are bioactive in isolated murine follicles.